Representação da informação em arquivos permanentes: um olhar sobre a análise documentária - Aguiar, Dyego Miguel Vicente de (2020)
The representation and retrieval of information in archives, especially in permanent archives, requires skills such as comprehension, analysis and synthesis, based on techniques, carried out by the Archivology professional, in a more precise way, considering that the permanent collection is of paramount importance with a view to assisting research and preserving memory. Documentary Analysis (DA) is one of the methodological procedures that assist the Archivist in this first stage of representation, and it is from his methods that this professional is able to extract the information necessary for future research on the document. Thus, this study highlights aspects of the importance of DA for the representation and retrieval of information in permanent files, specifying its concepts and purpose. For the development of the research and its application, the current situation of the Fund of the Polytechnic School, belonging to the permanent archive of the Federal University of Campina Grande (UFCG), has been analyzed, since this is a collection of great relevance in the history of the City, and its treatment deserves a special look. The approach aimed to awaken the institutions, especially the UFCG General Archive, and also Information Science professionals, about the final result of the recovery work carried out in the permanent archives, since it depends firmly on how the DA process was elaborated, to highlight the need for investments and greater preparation for using the procedures in reading the documents. With a view to carrying out the research, the following general objectives were taken: Proceeding the Archival functions of the Fund of the Polytechnic School of UFCG, based on Documentary Analysis; and, as specific objectives: Diagnose the documentation of the Polytechnic School Fund (FEP); Propose the application of the classification plan in the FEP; Specify the Archival Description areas used in the FEP based on NOBRADE; Describe the AtoM Software as an instrument for the representation and retrieval of FEP information; Contribute to the visualization of the information representation process of the Polytechnic School Fund documentation. To achieve the objectives, the investigation was conducted by an exploratory-descriptive research, specifically directed to the Fund of the Polytechnic School, held by the UFCG. The analyzes presented as a conclusion that the theoretical principles of the DA attend the processes of analysis, synthesis and representation of the information in files and can help the archivists of the UFCG to carry out the Archival Description of the Polytechnic School Fund, based on its analytical and synthetic steps presented Cândido (2014) and the levels of form and content of AD proposed by Pinto Molina (1989), guided by the NOBRADE guidelines. Thus, it was possible to conclude that the application of a Classification Plan in the Fund of the Polytechnic School will contribute to the organization and contextualization of the documentation in a hierarchical way in the fund and the implementation of AtoM as Software to represent the documentation of the FEP, will allow description in digital media, facilitating the access and diffusion of the information in the collection, which can now be done through a web environment.